Pathology-Based Animal Cancer Registry of Abruzzo and Molise Regions (Central Italy): A Ten-Year Retrospective Study (2014–2023) - Giovanni Di Teodoro; Francesca Cito; Romolo Salini; Marina Baffoni; Sabrina V. P. Defourny; Antonio Cocco; Nicola D’Alterio; Chiara Palmieri; Antonio Petrini (Veterinary Sciences)
Pets have a crucial role in cancer research. Specifically, dogs and cats share the same environment as their owners and thus may serve as sentinels of naturally occurring tumors that are linked to the exposure to environmental hazards. Quantitative comparison of tumor types may reveal unusual cancer frequencies, providing directions for research and generation of hypotheses of cancer causation in a specific area and identification of risk factors. The aim of this study was to describe the data collected by the pathology-based animal cancer registry, managed by Istituto Zooprofilattico Sperimentale dell’Abruzzo e del Molise (IZSAM), during 10 years of activity (2014–2023) and to assess its potential epidemiological relevance. Frequencies of tumor topography and morphology in dogs and cats were described, analyzed and compared. Proportional morbidity ratios (PMRs) were calculated, taking into consideration some potential risk factors such as species, breed, sex, diet and living environment. The database comprises 5311 tumors (n = 4719 in dogs and n = 592 in cats), with a higher prevalence in females (67.3% in dogs and 61.2% in cats). The mean age at the first diagnosis of tumors was similar between sexes and slightly lower in dogs compared to cats. PMRs highlighted certain risk and “protective” factors for the development of tumors in specific topography. The risk of developing tumors of the blood and hematopoietic system (PMR = 0.44; 95% CI: 0.21–0.94), skin and subcutaneous tissues (PMR = 0.70; 95% CI: 0.61–0.80), oral cavity and pharynx (PMR = 0.60; 95% CI: 0.24–0.89), urinary organs (PMR = 0.33; 95% CI: 0.11–0.99) and bones, joints and cartilage (PMR = 0.72; 95% CI: 0.22–0.98) was lower in non-neutered male dogs than in neutered male dogs. Non-spayed female dogs had a greater risk of developing tumors of the mammary gland (PMR = 1.75; 95% CI: 1.57–1.96), female sexual organs (PMR = 2.12; 95% CI: 1.01–4.36) and respiratory system (PMR = 2.25; 95% CI: 1.55–6.74) but less risk for cutaneous and subcutaneous tissue tumors (PMR = 0.44; 95% CI: 0.38–0.51) and blood/hematopoietic system tumors (PMR = 0.47; 95% CI: 0.26–0.85) compared to spayed female dogs. Compared with mixed breed, purebred dogs had a significantly greater risk of developing mammary gland tumors (PMR = 1.36; 95% CI: 1.20–1.54) and lower risk for respiratory (PMR = 0.15; 95% CI: 0.07–0.32), gastrointestinal (PMR = 0.63; 95% CI: 0.34–0.94) and oral (PMR = 0.59; 95% CI: 0.36–0.96) neoplasia. Non-neutered male cats had a lower risk of developing skin and subcutaneous tumors (PMR = 0.68; 95% CI: 0.50–0.92) compared with neutered cats. The risk of developing skin and subcutaneous tissues tumors was higher for dogs and cats that lived mostly outdoor (PMR dogs = 1.21; 95% CI: 1.10–1.33; PMR cats = 1.18; 95% CI: 1.08–1.47), while dogs that live mainly indoor had a greater risk to develop mammary gland tumors (PMR = 0.78; 95% CI: 0.68–0.89). Results described herein highlight the fundamental role of animal cancer registration initiatives. These efforts would contribute to the possibility of conducting multicentric collaborative studies to deepen the knowledge of the epidemiology of tumors in dogs and cats from a comparative perspective, thus fulfilling the One Health approach.